Mussel-inspired adhesive protein-based electrospun nanofibers reinforced by Fe(iii)–DOPA complexation. Issue 1 (4th November 2014) - Kim, Bum Jin; Kim, Sangsik; Oh, Dongyeop X.; Masic, Admir; Cha, Hyung Joon; Hwang, Dong Soo
Abstract : The mechanical properties of mussel-inspired electrospun nanofibers were reinforced by the Fe(III)–DOPA complex in the mussel adhesive protein, a key component for a naturally occurring high performance mussel protective coating. Abstract : Marine mussels utilize multiple bidentate complexes formed by Fe(iii ) and DOPA in a mussel adhesive protein (fp-1) to reinforce tough and elastic byssal fibers as a specialized underwater adhesive aid. In this study, mussel-inspired electrospun nanofibers were fabricated using a recombinant mussel adhesive protein ( r fp-1), Fe(iii )–DOPA complexes, and polycaprolactone. The mechanical properties of the fabricated nanofibers were reinforced by the Fe(iii )–DOPA complex found in fp-1, which is a key component of the naturally occurring high-performance mussel fiber coating. Experimental results show that the stoichiometry of Fe(iii )–DOPA complexes in the nanofibers could be controlled by buffer pH conditions and the stiffness of the nanofiber mat increased linearly with the concentration of the Fe(iii )–DOPA complexes, as monitored by resonance Raman spectroscopy. This suggests the potential of Fe(iii )–DOPA complexation as an effective strategy for modulating the mechanical properties of nanofibrous biomedical materials by using pH variations.